Learning from Malin Kundang: Developing Children’s Character through Moral Values in Fairytales - Estillomo, Ryan Besa; White, Ani Pujiastuti; Maskan, Olivina; Ginting, Michael Tongging (Publikasi Pendidikan, 2023)
ABSTRACTInvolving fairy tales and traditional stories in teaching is an effective method to increase children’s literacy skills and cognitive development. Rich narratives, moral lessons, and cultural contexts found in folktales contribute to children's reading comprehension, vocabulary expansion, and overall engagement with reading. Based on these statements, a recent community service program conducted by the Literacy in Education course at President University staged a play performance of the Indonesian folktale Malin Kundang for elementary school students. This program was conducted at the President University Auditorium to commemorate Indonesia's National Children's Day. The program was collaboratively organized by students and lecturers from diverse majors. The participants of the program comprised first to third grade elementary school students from the Jababeka area in West Java, members of the Faculty of Humanities, and students from the Primary School Teacher Education study program. The children responded very positively to the activity, gaining memorable lessons on moral values and love of fairy tales. Furthermore, the collaboration between lecturers and students enhanced skills in teamwork, creativity, and shared social responsibility. In light of the findings, the integration of fairy tales into educational programs stands as a promising approach to literacy and character education in children.Keywords: fairy tales, literacy development, moral values, community service